1999
DOI: 10.1093/ee/28.3.431
|View full text |Cite
|
Sign up to set email alerts
|

Coprophagy Facilitates Horizontal Transmission of Bait Among Cockroaches (Dictyoptera: Blattellidae)

Abstract: Baits offer several advantages over other insecticide formulations in the control of populations of the German cockroach, Blattella germanica (L.). However, they may fail to target certain life stages that feed only sparingly. Recently we have demonstrated that 1st instars are signiÞcantly more vulnerable to insecticidal baits when adults are present. By preventing adults or nymphs from eating bait we now conclude that adults translocate insecticide bait to the shelter, thus facilitating a horizontal transfer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…A number of effective, non‐repellent active ingredients have been incorporated within baits . Modern bait formulations can kill cockroaches through direct ingestion (primary kill), as well as through the uptake of translocated AI (secondary kill), whereby cockroaches, primarily first‐instar cockroach nymphs, are adversely affected following ingestion of (coprophagy) or contact with excretions containing the toxicant . Secondary kill through coprophagy is especially effective with slow‐acting AIs, such as hydramethylnon …”
Section: Introductionmentioning
confidence: 99%
“…A number of effective, non‐repellent active ingredients have been incorporated within baits . Modern bait formulations can kill cockroaches through direct ingestion (primary kill), as well as through the uptake of translocated AI (secondary kill), whereby cockroaches, primarily first‐instar cockroach nymphs, are adversely affected following ingestion of (coprophagy) or contact with excretions containing the toxicant . Secondary kill through coprophagy is especially effective with slow‐acting AIs, such as hydramethylnon …”
Section: Introductionmentioning
confidence: 99%
“…The donor termites delivered active ingredient into their respective colonies through mutual grooming and propagated the spread of active ingredient by trophallaxis. Kopanic and Schal (1999) showed that sedentary Þrst and second instars of German cockroach, Blattella germanica L., received lethal doses of hydamethylnon by consuming adult excreta (coprophagy) at aggregation sites. The use of a slow-acting insecticide, such as hydramethylnon, was important because most of the active ingredient was excreted 12-h postconsumption.…”
mentioning
confidence: 99%
“…None of these experiments separated the role of coprophagy and cannibalism from that of contact with traces deposited on dead bodies and feces. As intestinal transit takes longer than Þpronil to kill cockroaches (Kopanic and Schal 1999), dispersion of Þpro-nil by feces is then negligible. Contamination through feces is much more likely to occur when feces fall on traces already deposited in the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors are responsible for secondary transmission. Kopanic and Schal (1999) showed the action of coprophagy whose role is limited by intestinal transfer lasting at least 12 h. Gahlhoff et al (1999) demonstrated the role of cannibalism of dead contaminated cockroaches.…”
mentioning
confidence: 99%